Impact of Implant Surface and Smoking on Peri-Implant Human Bone: What we Learned from The Last 20 Years? - Shibli, Jamil Awad (2024)
The present review summarizes the findings from human histological studies conducted over the past 20 years at the University of Guarulhos, Brazil, examining the impact of various implant surface topographies and smoking on peri-implant bone response. Seven different implant surfaces were evaluated in 90 partially or completely edentulous individuals using a total of 123 micro-implants. Histometric parameters, including bone-implant contact (BIC%), bone area within the threads (BA%), and bone density (BD), were assessed after an 8-week healing period. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) analyses were also performed. Results showed that treated surfaces, regardless of the treatment type, consistently demonstrated better histometric outcomes compared to machined surfaces. Anodized surfaces and those subjected to airborne particle abrasion, followed by acid etching, exhibited higher BIC% values than machined surfaces in smoker patients. Smoking reduced BIC% around anodized implants. The presence of inflammatory cells was observed adjacent to the peri-implant soft tissue on some treated surfaces. In conclusion, implant surface topography significantly influences early bone response under unloaded conditions, with treated surfaces promoting better human bone tissue response than machined surfaces. However, smoking negatively impacts peri-implant bone healing, emphasizing the importance of smoking cessation for optimal osseointegration.